The top 10 of everything 2004 - Ash, Russell, author 543141 (London : Dorling Kindersley, 2003)
A collection of facts and trivia features more than one thousand lists that cover a broad range of subjects, including culture and learning, sports, the universe and the Earth, and the human world.